Geriatric Mental Health Nursing in India: Need and Scope - K. Annapoorani; Radhakrishnan Govindan; Palanimuthu Thangaraju Sivakumar; K. S. Meena; G. Balamurugan (Indian Journal of Psychiatric Nursing)
India’s aging population is witnessing a surge in geriatric mental health concerns, with conditions like depression and dementia affecting a significant proportion of older adults. Geriatric mental health nursing (GMHN) plays a critical role in early detection, holistic care, and enhancing the quality of life for this vulnerable group. Despite its growing importance, the field faces significant workforce shortages and limited training opportunities. Initiatives such as the fellowship in GMHN at NIMHANS mark progressive steps toward building specialized capacity. Integrating GMHN into nursing curricula and expanding structured programs are essential to meet future needs. Strategic policy changes, enhanced career pathways, and investment in this niche field are crucial for sustainable impact.